Pembangunan Sistem Informasi Monitoring dan Evaluasi Pelayanan Kesehatan Orang Dalam Gangguan Jiwa (ODGJ) berbasis Web dengan Metode Waterfall - Muhammad Hasan Johan Alfarizi; Komang Candra Brata; Ahmad Afif Supianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Health services are a solution for preventing health disease, improving health, and health treatment by the government and society. To meet the level of health services, there are procedures in the preparation of annual needs planning in the RKPD (Regional Government Work Plan). The problem that occurs is in the process of reporting data received from each puskesmas for handling people with ODGJ (People with Mental Disorders) because the data reporting techniques received by the government from the puskesmas still use conventional methods. In overcoming this, a monitoring and evaluation information system is needed to make it easier for each puskesmas to report health service activities so that monitoring and evaluation can be carried out by the central government of the results of each puskesmas need in order to predict the need for health services in each region. This information is built using the waterfall method with a pre-made design so that it has clear needs at the beginning of development. the results carried out on the testing unit and the valid test produce 100% valid in all test cases, while the compatibility test results in 26 valid, 2 major issues, and 1 minor issue in 9 browser versions with the SortSite tool.